Pengaruh Elektronikal Marketing terhadap Minat Wisatawan Berkunjung ke Pulau Saronde - Ali Hasan; Irma Kharisma Hatibie (Media Wisata, 2014)
The purpose of the authors conducted research to determine the effectiveness of E-Marketing Interests Against Tourist Visits in Gorontalo Saronde Island and can be beneficial for the institutions, the object of research, author and upcoming research. The location of the research is Saronde Island in Gorontalo. E-Marketing is one of the factors that play an important role in running a marketing business. E-marketing or Electronic Marketing is one of the breakthroughs that are quite reliable in marketing a tourism product. Saronde Island as one of the tourist attractions managed by GAB (Natural Gorontalo Maritime) uses the concept of E-Marketing as one way powerful enough to market their products. This research uses quantitative, measurement data in the form of numbers. Variables examined include Facebook marketing, email marketing, web marketing and blackberry messenger marketing. The number of samples from the total sample is 60 respondents to the normality test, autocorrelation test results and test multilinear data formula that relies on the analysis of the results of Durbin Watson and VIF (Variance Inflation Factor). With the technique of multiple regression analysis. The analysis result showed Blackberry Messenger is the most effective changer variable, which conducted to influent visiting of tourists, than others variable. The results showed a significant effect on the interest in visiting tourists at Saronde island of Gorontalo. The implications of this study are to be helpful to the reader, or for anyone who wants to continue the same thing in future research. Hypothesis Testing depends variable to the independent variable, the probability value is < 0.01.